Antimicrobial photodynamic therapy for managing the peri-implant mucositis and peri-implantitis: A systematic review of randomized clinical trials - Rashin Bahrami; Nariman Nikparto; Fateme Gharibpour; Maryam Pourhajibagher; Abbas Bahador (Photodiagnosis and Photodynamic Therapy)
Background: The presence of peri‑implant inflammation including peri‑implant mucositis and peri‑implantitis, is a crucial factor that impacts the long-term stability and success of dental implants. This review aimed to evaluate the safety and effectiveness of antimicrobial photodynamic therapy (aPDT) as an adjuvant therapy option for managing peri‑implant mucositis and peri‑implantitis. Methods: We systematically searched the PubMed/MEDLINE, Cochrane Library, Scopus, and Google Scholar databases (no time limitation). The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the quality of the studies was assessed using the Cochrane Collaboration tool. Results: Of 322 eligible articles, 14 studies were included in this review. The heterogeneity and poor quality of the articles reviewed prevented a meta-analysis. The reviewed articles used a light source (60 s, 1 session) with a wavelength of 635 to 810 nm for optimal tissue penetration. These studies showed improved clinical parameters such as probing depth, bleeding on probing (BOP), and plaque index after aPDT treatment. However, in smokers, BOP increased after aPDT. Compared to conventional therapy, aPDT had a longer-term antimicrobial effect and reduced periopathogens like Porphyromonas gingivalis, as well as inflammatory factors such as Interleukin (IL)-1β, IL-6, and Tumor necrosis factor alpha (TNF-α). No undesired side effects were reported in the studies. Conclusion: Although the reviewed articles had limitations, aPDT showed effectiveness in improving peri‑implant mucositis and peri‑implantitis. It is recommended as an adjunctive strategy for managing peri‑implant diseases, but further high-quality research is needed for efficacy and long-term outcomes.